Metodología de cobro para los servicios auxiliares brindados por la subestación Garita - Soto-Hernández, César Alonso (Instituto Tecnológico de Costa Rica, 2018)
Currently, the Costa Rican Electricity Institute (ICE), in the substations, provides auxiliary services corresponding to direct current (130 V) and alternating current (120/208 V). These auxiliary services were not previously charged among ICE's internal clients, but ICE is currently looking for efficiency and control of the business and of the areas expenses, which is why a collection methodology was established that meets this need, and it must also comply with the requirements of sectorial regulation on electrical services in chapter 4, article 22 of the ARESEP. This methodology covers only the La Garita electrical substation, which by applying the collection methodology for direct current auxiliary services, it was possible to identify that the beneficiaries and their associated costs correspond to 6% Cence, 8% Generation Business, 11% Transmission Business, 16% Communication Area, 23% Chucás, 36% Distribution Business, the costs represent around ₡ 3,800,000.00 monthly and ₡ 45,000,000.00 annually. In addition to the collection methodology for auxiliary services alternating current , the following results obtained as beneficiaries and costs refer, 14% to the Operations Area, 21% to the Civil Area, 22% to the Direct Current Area and 43% to the high voltage area, which represents a cost total of around ₡ 2,200,000.00 monthly and ₡ 27,000,000.00 annually.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Costos; Servicios; Metodología; Cobros; Clientes; Beneficiarios; Research Subject Categories::TECHNOLOGY::Engineering mechanics